VIAF and the linked data ecosystem - Putnam, Nathan (JLIS.it, 2022)
This article reviews the founding, current state, and potential future of VIAF®, the Virtual International Authority File. VIAF consists of an aggregation of bibliographic and authority data from over 50 national agencies and infrastructures, systems that follow different cataloging practices and contain hundreds of languages. After a short history of the project, the results of surveys for implementers of linked data projects on the use of VIAF data and provides suggestions for future use and sustainability